Antidepressant Activity Of 80% Bitter Melon-Leaf Ethanol Extract (Momordica Charantia L.) And ? -Sitosterol Compound In Vivo - Ani Kristiyani; Zullies Ikawati; Andayana Puspitasari Gani; Zaenal Muttaqien Sofro (Jurnal Ners, 2025)
Depression is a psychiatric disorder that affects mood and physical health and contributes greatly to the global burden of disease. Herbal remedies can be used as an alternative to the treatment of depression. The purpose of this study is to determine the activity of 80% ethanol extract of bitter melon leaves (Momordica charantia Linn) as an antidepressant and ?-sitosterol compound which is a marker compound in bitter melon leaf extract. In this study, ?-sitosterol compounds in bitter melon leaf extract were identified qualitatively using Fourier Transform InfraRed (FTIR) and in vivo antidepressant activity tests. The in-vivo test used 30 mice with a weight of 20-30 grams which were randomly divided into 6 groups, namely the normal group (not receiving treatment), the negative control group (Na-CMC 1%), the positive control group (fluoxetine 2.5 mg/kg), the ?-sitosterol group (?-sitosterol 30 mg/kg), the bitter melon leaf extract group dose 1 (200 mg/kg), and the group of bitter melon leaf extract dose 2 (400 mg/kg). The mice received stressors using the Chronic Unpredictable Mild Stress (CUMS) method for 28 days. On the 15th day after the mice received CUMS, the mice were exposed to test extracts and drugs for 14 days according to the treatment group. Weight measurements were taken on day 1 and on day 29. The behavioral test used the Forced Swimming Test (FST) and Novel Suppressed Feeding (NSF) with feeding time parameters, and the immobility time was carried out on the 29th day, in addition to that the number of necrosis in gastric and the number of hippocampal pyramidal cells were also measured. The results showed that at all absorption peaks in the FTIR of bitter melon leaf extract, there were -OH, C-H, C=C, - CH2-, C-O groups which are the characteristic peaks of the ?-sitosterol compound. In weight measurement, bitter melon leaf extract had antidepressant activity by not causing significant weight changes compared to the normal group (P>0.05). The ?-sitosterol and bitter melon leaf extract group dose 2 had antidepressant activity by maintaining appetite which was shown with a higher feeding time value compared to the negative group (P<0.05). The positive control group, ?-sitosterol, and bitter melon leaf extract doses 1, and 2 when compared to the negative control group, although not significant (P>0.05) had antidepressant activity values by lowering despair indicated by smaller immobility time values, lowering the number of necrosis in gastric lower and protecting the hippocampal pyramidal cell count higher. Conclusion: 80% ethanol extract of bitter melon leaves contains active compounds ?-sitosterol and has activity as an antidepressant by not causing weight changes, maintaining appetite, lowering despair, protecting gastric from necrosis and protecting hippocampal pyramidal cells.